Short-term outcome in acute and transient psychotic disorder and its correlate to various sociobiological factors - Chandak, Sumit; Gowda, Sunil N. (International Journal of Advances in Medicine, 2017)
Background: There is a higher incidence of acute and transient psychotic disorder, however there are not much data on the course of disease and its association with sociobiological factors. We assessed the outcome in patients who met the ICD 10 DCR criteria for acute and transient psychotic disorder, at a follow up period of 6 months. Methods: We conducted a prospective observational study conducted at out-patient department of the Institute of Psychiatry and Human Behaviour, Bambolim, Goa. Fifty-seven patients were enrolled and were followed up for a period of 6 months from the day of enrollment. The outcome was ‘review of diagnosis and ‘no review of diagnosis at the end of 6 months. Results: The mean age of the study sample was 32.25 years. In three-fourth of the patients, there was no change in the diagnosis. Nearly 65% of the patients were women and 35% of them were men. No review in diagnosis was made in significant proportion of the population. Average duration of education was 7.35 years. Most of them were unskilled laborers and homemakers. A significant number of the study population was migrants. Two-third of the population did not have any family history of psychiatric disorder. The onset was acute in majority of the patients. Suicidal thoughts were present at the time of diagnosis in certain patients. The treatment adherence was lower in those whose diagnoses did not change at the end of 6 months. Sleep disturbances, ideas of persecution, and concentration difficulties were the frequently reported symptoms.No repeat episodes were noted in our study. Conclusions: No review in diagnosis was made in significant proportion of the population. The treatment adherence was lower in those whose diagnoses did not change at the end of 6 months.